Do hospital-to-home transitions work for older adults with multiple long-term conditions including dementia? A realist review - Lauren Lawson; Matthew Cooper; Clare Tolley; Annette Hand; Hamde Nazar (BMC Geriatrics)
Abstract Background Hospital-to-home transitions involve multiple providers and are particularly complex for older adults with dementia, who often live with additional conditions. Frequent transitions increase the risk of errors, miscommunication, and treatment delays, compromising patient safety and leading to potentially increased mortality, morbidity, and preventable readmissions. Understanding what works and does not work in these processes is essential to improving outcomes. Aim This realist review synthesised existing literature to explore how, for whom, and to what extent hospital-to-home transitions work for older adults with multiple long-term conditions including dementia. Methods Nine databases were systematically searched using key terms to identify evidence on hospital-to-home transitions for older adults (65+) with multiple long-term conditions including dementia. Interactions between contexts, mechanisms, and outcomes influencing transitions were identified and synthesised to develop a programme theory. Results We included 68 peer-reviewed and 2 grey literature documents. Integral features of how transitions work were identified, including generic components of transitions, and five dementia-specific components which were the focus of this review: dementia care management, knowledge, information exchange standards, system features, and the role of friends/family. Fragmented care pathways and poor collaboration led to delays, unsafe discharges, and increased reliance on carers, exacerbating service gaps. Limited dementia training for providers and non-standardised documentation hindered effective discharge planning. Carers faced emotional distress and decision-making conflicts, often managing care responsibilities without adequate training, increasing risks of readmissions, particularly for unmanaged conditions. Conclusions Hospital-to-home transitions are complex, requiring tailored interventions that address population-specific challenges. A realist approach provides valuable insights to inform development of relevant, supportive interventions in the future. Study registration This review was preregistered with PROSPERO (CRD42023494003). Clinical trial number Clinical trial number: not applicable.